GIS-based quantitative landslide hazard prediction modelling in natural hillslope, Agra Khola watershed, central Nepal - Thapa, Prem Bahadur; Esaki, Tetsuro (Bulletin of the Department of Geology, 2008)
The influence of geological and geomorphological variables were spatially integrated to develop landslide hazard prediction model in the Agra Khola watershed of central Nepal where a large number of landslides triggered off due to extreme weather event of July 19-21, 1993. A quantitative technique of multivariate analysis was performed to predict elements or observations of landslides successfully into different hazard levels in the area. The predicted landslide hazard was validated and spatially relevancy of the prediction is established. The GIS-based prediction model possessed objectivity and reproducibility, and also improved the landslide hazard mapping in the natural hillslope. doi: 10.3126/bdg.v10i0.1421   Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 63-70